Real-time Vehicle Detection System Based on Video Image - LIU Changyuan,CAO Yuanyuan,LUO Yiming (Jisuanji gongcheng, 2019)
To solve the problem that the detection efficiency and accuracy of the real-time monitoring system for vehicle are low,a real-time vehicle detection system is designed.First,the system grayscales,filters,and enhances the video images to segment the statistical regions.Then,in the segmentation image,the statistical mode method is designed to construct the background model and the Canny operator is used to detect the vehicle edge.At last,the foreground and vehicle edge images are superimposed for morphological operation to obtain the vehicle counting.Experimental results show that the accuracy of the system is up to 98.45%,which can meet the needs of intelligent transportation systems for detection efficiency and accuracy.